Wärmeübergang in kurzen, wandgängig gerührten Apparaten. Issue 8 (2nd April 2014) - Hillmann, Jörg; Walzel, Peter
<x xml:space="preserve">Abstract</x> Scraped surface heat exchanger are often used in industrial settings for the treatment of systems with solid particle formation or higher viscosities. In reactors with a small length‐diameter ratio, the backmixing has thereby a significant influence on the heat transfer. In the experiments presented here, it can be shown that the heat transfer coefficient strongly depends on the flow pattern within the laminar flow regime, and that, depending on the running conditions, an increased rotor speed may have a negative effect on the heat transfer rate.